Long‐term care facilities' response to the COVID‐19 pandemic: A protocol of a cross‐sectional, multi‐site, international survey - Sameh Eltaybani; Haruno Suzuki; Ayumi Igarashi; Mariko Sakka; Yuko Amamiya; Noriko Yamamoto‐Mitani (Wiley, 2022)
Abstract Aim To examine the response of long‐term care (LTC) residential facilities to the COVID‐19 pandemic worldwide, and the antecedents and outcomes of this response. Design A protocol of a cross‐sectional survey. Methods Two online questionnaires will be used to collect data from LTC residential facilities' managers and staff worldwide. Collected data include participants' socio‐demographic characteristics, facility‐related characteristics, facility response to the COVID‐19 pandemic, and possible influences of the pandemic on staff, residents, and residents' families. Data collection has started in April 2021. Data analyses will be conducted on the pooled sample and stratified by the type of facility, participants, or country if required. Multi‐level regression analysis will be considered to account for participants' data clustering in countries and facilities. Results The data collection is ongoing. The findings would guide policy‐makers and healthcare organizations to reform their protocols for the best interest of facilities, staff, residents, and residents' families.